Keberadaan Radio Komunitas sebagai Eskalasi Demokratisasi Komunikasi pada Komunitas Pedesaan di Jawa Barat - Rachmiatie, Atie (FIkom Unisba, 2005)
The main problem researched in this thesis was the existence of community radios in villages, that was about the roles of function of them correlated with the escalation of democratization in communication. The research was conducted in two Kecamatans that had different characteristics, that was Kecamatan Cisewu which was minim in any information exposure and geographically closed (blank spot) and Kecamatan Wanayasa which was relatively open to access any information. The theory used to study the problem were Habermas Communicative society theory and Uses and Dependency theory. The theory explained the correlation between social system and communication media system at a community. The democratization of communication was explained by Communitarianism Democracy Theory – Tehranian. The research method used was qualitative method with etnography communication. Data were collected through depth interview and focus group discussion. The key informan woman were formal and informal social leaders and the person who managed community radios. Focus group discussion was conducted to group of women, men, youths, and others ot both of kecamatans. Analysis of etnography of communication try to explore the native language, that was sundanese, used by the member of community, wether with or without community media. The result of the research is accordance with research question.The availability contribute awwarness about communication and information right for the community members. The public community process through radio community is the implementation of the daily public behaviour pattern of the community. The process of democratization communication run slower in the closed area, yet it is more dynamic in the opened area.